Enhanced Upconversion Luminescence of Metal‐Capped NaGd0.3Yb0.7F4:Er Submicrometer Particles. Issue 15 (3rd March 2016) - Li, Ai‐Hua; Lü, Mengyun; Guo, Ling; Sun, Zhijun
Abstract : Metallic nanostructures are often used to enhance photoluminescence of nanomaterials based on local field enhancement with plasmons at metal surfaces. Here upconversion luminescence (UCL) enhancement of submicrometer‐size NaGd0.3 Yb0.7 F4 :Er particles in cap‐like metal cavities, formed by deposition of a silver film on the particles dispersed on glass substrates, is studied. UCL of the particles is shown to be influenced by not only the plasmon‐enhanced local field but also the cavity modes. By varying the cavity size and location of the particles in the cavities, fluctuant variations of the UCL enhancement and electronic depopulation rate are observed in experiments. Typically, a maximum of 12‐fold enhancement of the UCL intensity is obtained. Combining the results with numerical simulations, the phenomenon is ascribed to effects of metal quenching, plasmonic field enhancement, and the cavity modes for the excitation and emission photons. Finally it is verified that, for the cap‐like submicrometer metal cavities, allocating the particles at the open mouths of the cavities is more advantageous to obtaining stronger enhancements of the particles' UCL. And the demonstrated structure is also convenient to fabricate for applications, e.g., in solar cells. Abstract : Upconversion luminescence of metal‐capped submicrometer‐size NaGd0.3 Yb0.7 F4 :Er particles is enhanced and modulated by the localized plasmon and cavity mode fields. Except for the large enhancement factor obtained, variation in the luminescence efficiency with respect to the cavity size is analogous to that of emitters near a planar metal surface with their photoluminescence dependent on the emitter‐to‐metal‐surface distance.